VHS203E- Modern Asian Art (Seni Moden Asia) 2022/2023 - PPS, Pusat Pengajian Seni (2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 VHS203E- Modern Asian Art (Seni Moden Asia) Duration : 2 hours (Masa : 2 jam)